Exploring Learners’ Experiences with Clinical Ethics Consultations: A Narrative Reflection on the Impact and Role of Emotions - Christopoulos, Téa; Sobode, Oluwaseun; Bailey, Megan; McKibbon, Dylan; Milovac, Thomas; Moshiri, Sam; Van Leeve, Jessie (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
As clinical ethics learners, we have observed ethics consultations and have experienced an array of emotional responses as a result of these consultations, particularly surrounding topics pertaining to end-of-life decision-making. While there is extensive literature on the role and nature of emotions for many frontline healthcare providers, such as nurses and physicians, limited research exists on the emotional experiences of clinical ethicists and clinical ethics learners. We maintain that understanding these emotional experiences can deepen our understanding of the role and practice of clinical ethicists, especially given the challenging and values-laden healthcare contexts in which ethics consultations often occur. This research can also inform current and future ethics education to aid in the development of quality-driven training programs for future ethicists, such as bioethical simulation labs. This paper sought the voluntary contributions of seven clinical ethics learners, who provided a narrative account of their experiences with clinical ethics consultations as a means to identify key themes related to emotional responses to ethics consultations.